BARRIERS FACED BY CENTRAL ASIAN MIGRANTS IN THE U.S. IMMIGRATION SYSTEM - Kamronbey Kenjaev (International Journal of Business, Law and Political Science, 2026)
Objective: This essay examines forms of complexity with the U.S. immigration system that are multifaceted barriers for migrants from Central Asia. It examines the legal, social, and economic barriers to their successful resettlement. Method: The study analyzes legal, social, and economic dimensions of migration barriers, including complex visa processes, long delays and limited access to legal advice, as well as language barriers, cultural adjustment difficulties, discrimination, limited access to the formal labor market, underemployment and wage gaps. It also considers the role of support services, such as community organizations, legal aid and language training programs, in addressing these challenges. Results: Among other barriers, complex visa processes, long delays and limited access to legal advice lead to uncertainty and stress for migrants. Social obstacles include barriers to language, difficulties in adjusting to a new culture and discrimination encountered in everyday life as well as at work. From an economic perspective, migrants are frequently faced with limited access to the formal labor market, underemployment and wage gaps. The study also highlights the importance of support services in addressing these challenges. Novelty: Last, the article broaches policy recommendations to mitigate these barriers and promote equitable conditions that foster the successful incorporation of Central Asian migrants in U.S. society.